2014
DOI: 10.1002/jms.3373
|View full text |Cite
|
Sign up to set email alerts
|

New covalent modifications of phosphatidylethanolamine by alkanals: mass spectrometry based structural characterization and biological effects

Abstract: The pathophysiology of numerous human disorders, such as atherosclerosis, diabetes, obesity and Alzheimer's disease, is accompanied by increased production of reactive oxygen species (ROS). ROS can oxidatively damage nearly all biomolecules, including lipids, proteins and nucleic acids. In particular, (poly)unsaturated fatty acids within the phospholipid (PL) structure are easily oxidized by ROS to lipid peroxidation products (LPP) carrying reactive carbonyl groups. Carbonylated LPP are characterized by high i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 62 publications
1
20
2
Order By: Relevance
“…One more reason for the high reactivity of short chain dicarbonyls could be the relatively high hydrophilicity. It was demonstrated that peptides as relatively hydrophilic substrates preferentially react with shorter carbon chain aldehydes whereas aminophospholipids, as more hydrophobic compounds, are modified with longer chain carbonylated analogues [99].…”
Section: Resultsmentioning
confidence: 99%
“…One more reason for the high reactivity of short chain dicarbonyls could be the relatively high hydrophilicity. It was demonstrated that peptides as relatively hydrophilic substrates preferentially react with shorter carbon chain aldehydes whereas aminophospholipids, as more hydrophobic compounds, are modified with longer chain carbonylated analogues [99].…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the use of different ion activation modes as well as different ionization sources is a powerful tool to elucidate metabolite and drug structures in complex chemical mixtures . Understanding the fragmentation behavior and the product ions of FA under different MS conditions can help elucidate the structure of FA analogs, as well as facilitate identification of new candidate molecules …”
Section: Introductionmentioning
confidence: 99%
“…The MS spectrum of the reaction products are shown in Figure , which clearly depicts the characteristic mass shifts of 120 Da, 138 Da, 156 Da, corresponding to cyclized Schiff base (a), Schiff base (b), and Michael adduct (c), respectively. More recently, Annibal et al () employed high‐resolution Orbitrap MS analysis to identify modified derivatives of 1,2‐dipalmitoyl‐ sn ‐3‐glycerophosphoethanolamine (DPPE) arising from its incubation with hexanal and other alkanals. The MS spectrum of the products of the reaction between DPPE and hexanal acquired in positive ion mode, shown in Figure A, shows new ions that have mass shifts corresponding to the sequential adductions of up to three hexanal molecules, resulting in a series of monomeric, dimeric, and trimeric covalent adducts.…”
Section: Ms‐based Strategies For the Analysis Of Apl Modificationsmentioning
confidence: 99%
“…The ion at m/z 692.52 corresponds to [M+H] + molecular ion of DPPE; the ion at m/z 774.60 corresponds to the Schiff base adduct (mass shift of 82 Da); the ion at m/z 856.68 corresponds to the dimeric adduct, arising from the covalent adduction of a second molecule of hexanal (mass shift of 164 Da), the ion at m/z 874.69 was identified as the hydrated form of this dimer; the ion at m/z 936.74 corresponds to the pyridinium ring adduct formed by covalent adduction of a third hexanal molecule, followed by cyclization and loss of one H 2 O molecule; the ion at at m/z 954.75 corresponds to the hydrated precursor of the pyridinium adduct; the ion at m/z 938.76 corresponds to the trimeric adduct. The mechanism of the consecutive covalent adductions of hexanal to DPPE is resumed in Panel B. Reprinted with permission from Annibal et al (), copyright 2014 [John Wiley & Sons].…”
Section: Ms‐based Strategies For the Analysis Of Apl Modificationsmentioning
confidence: 99%
See 1 more Smart Citation